NGANDAGAN LAMPAU DAN KONTEMPORER (Sebuah Telaah Perubahan Agraria di Desa Ngandagan, Jawa Tengah) - Risma Junita (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2013)
Indonesia is known as an agricultural country that rich in agricultural resources. Talking about agrarian problems, can not be separated from the study of the agrarian tenure systems, especially land. During the past years, known as one of the land tenure system is communal tenure systems. In a village located in the province of Central Java, Ngandagan Village, such mastery system is also available and applied. To be interesting to analyzed when communal land tenure system is transformed into a tenure system that contains the values of innovation tenure in Ngandagan Village, through the role of a village leader. This paper aims to review and analyze the current context Ngandagan village conditions. Review and analysis are based on two bookswhich telling abaut past condition and contemporary condition of Ngandagan village. In particular, this report is organized to identify and analyze some of the main things that happened in the village of Ngandagan, namely: agrarian change, the situation or circumstances behind the change in the agrarian, the agent who plays a role in the agrarian change, kind of impact arising from the agrarian change to the distribution of land ownership and to the socio-economic aspects of society. The agrarian changes related to the control system of agrarian resources and agrarian relationship.Soemotirto headman is someone who leads a government organization in Ngandagan, has been successfully using its strengths as a headman to make a few changes in the village. The impact of a agrarian change in Ngandagan can be viewed from two aspects, namely the impact on the distribution of land ownership and the impact on socio - economic aspects. The impacts make equity of access to the resources,remove of exploitative agrarian relationship and makethe increase of economic conditions with an increased level of well-being and more evenly.